A hybrid Phillips curve and consumer confidence: the case of Brazil. (2018) - Lopes, Thiago Henrique Carneiro Rios; Jesus, Cleiton Silva De; Rivera-Castro, Miguel Angel
The main aim of this paper is to verify the determinants of Brazilian inflation using a hybrid Phillips curve. Its innovation is in its incorporation of consumer confidence and by combining this with the unemployment rate as an explanatory variable in the empirical Phillips curve. The main results show that: (i) the effect of unemployment in reducing inflation occurs when the level of consumer confidence is below 125 and (ii) the level of consumer confidence is negatively influenced by both nominal exchange rate and unemployment shocks. This means that increasing unemployment does not necessarily reduce inflation. The unemployment rate needs to be high enough to reduce consumer confidence to the specific level at which a recessive policy can produce the expected effects.